Treating subthreshold depression in primary care: A randomized controlled trial of behavioral activation with mindfulness - Wong, S.; Sun, Y.; Chan, A.; Leung, M.; Chao, D.; Li, C.; Chan, K.; Tang, W.; Mazzucchelli, Trevor; Au, A.; Yip, B. (2018)
© 2018, Annals of Family Medicine, Inc. All rights reserved. PURPOSE We undertook a randomized controlled trial to assess the efficacy of group-based behavioral activation with mindfulness (BAM) for treating subthreshold depression in primary care in Hong Kong. METHODS We recruited adult patients aged 18 years or older with subthreshold depression from public primary care clinics and randomly assigned them to a BAM intervention group or a usual care group. The BAM group was provided with eight 2-hour weekly BAM sessions by trained allied health care workers. Patients in the usual care group received usual medical care with no additional psychological interventions. The primary outcome was depressive symptoms measured by the Beck Depression Inventory-II at 12 months. Secondary outcomes included incidence of major depressive disorder at 12 months. We assessed quality of life, activity and circumstances change, functional impairment, and anxiety at baseline, end of intervention, 5 months, and 12 months. RESULTS We randomly allocated 115 patients to the BAM intervention and 116 patients to usual care. At 12 months, compared with usual care peers, BAM patients had a slightly more favorable change in levels of depressive symptoms on the Beck Depression Inventory-II (between-group mean difference in score = –3.85; 95% CI, –6.36 to –1.34; Cohen d = –0.46, 95% CI, –0.76 to –0.16). Incidence of major depressive disorder was lower with BAM (10.8% vs 26.8%, P =.01), whereas groups did not differ significantly on other secondary outcomes at 12 months. CONCLUSIONS Group BAM appears to be efficacious for decreasing depressive symptoms and reducing the incidence of major depression among patients with subthreshold depression in primary care, although generalizability of our findings may be limited.